Congenital heart malformations induced by hemodynamic altering surgical interventions - Midgett, Madeline; Rugonyi, Sandra (Frontiers in Physiology, 2014)
Embryonic heart formation results from a dynamic interplay between genetic and environmental factors. Blood flow during early embryonic stages plays a critical role in heart development, as interactions between flow and cardiac tissues generate biomechanical forces that modulate cardiac growth and remodeling. Normal hemodynamic conditions are essential for proper cardiac development, while altered blood flow induced by surgical manipulations in animal models result in heart defects similar to those seen in humans with congenital heart disease. This review compares the altered hemodynamics, changes in tissue properties, and cardiac defects reported after common surgical interventions that alter hemodynamics in the early chick embryo, and shows that interventions produce a wide spectrum of cardiac defects. Vitelline vein ligation and left atrial ligation decrease blood pressure and flow; and outflow tract banding increases blood pressure and flow velocities. These three surgical interventions result in many of the same cardiac defects, which indicate that the altered hemodynamics interfere with common looping, septation and valve formation processes that occur after intervention and that shape the four-chambered heart. While many similar defects develop after the interventions, the varying degrees of hemodynamic load alteration among the three interventions also result in varying incidence and severity of cardiac defects, indicating that the hemodynamic modulation of cardiac developmental processes is strongly dependent on hemodynamic load.